Clinical study of cases of ruptured uterus in pregnancy - Vidyarthi, Anubha; Kumari, Santwana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Rupture uterus is a rare and often catastrophic condition. It is associated with a high incidence of fetal and maternal morbidity and mortality. It is a preventable condition. Timely diagnosis and management results in better outcome. The objective of this study was to determine incidence, risk factor, management, maternal and fetal outcome in cases of uterine rupture. Methods: A retrospective study of cases of ruptured uterus was done over a period of one year from January 2015 to December 2015. The case sheets of patients were traced through labor room register, operation theatre register and medical record section. Results: There were 57 cases of ruptured uterus out of total 8112 deliveries in labor room, giving incidence of 7.03/1000 deliveries (0.7%). The most common risk factor was previous caesarean section in 59.7% of cases. In 54.4% cases patients were multiparous (≥3). Most of the patients presented with poor general condition, abdominal pain and tenderness, palpable fetal parts and in shock in 68.4% cases. Patients were treated with immediate resuscitation and laparotomy followed by either repair or hysterectomy. There was high perinatal mortality of 89.5%. Maternal mortality was 3.5%. Conclusions: Proper antenatal care, appropriate counselling of patients with history of previous caesarean section for hospital delivery, training of skilled birth attendant can reduce mortality and morbidity associated with rupture uterus.